Left ventricular outflow tract obstruction and its impact on systolic ventricular function and exercise capacity in adults with a subaortic right ventricle. (1st October 2017) - Stauber, Annina; Wey, Céline; Greutmann, Matthias; Tobler, Daniel; Wustmann, Kerstin; Wahl, Andreas; Valsangiacomo Buechel, Emanuela R.; Wilhelm, Matthias; Schwerzmann, Markus; ,
Abstract: Background: In biventricular hearts the filling and contractility of one ventricle affects the performance of the other. In this study, we compared right ventricular systolic function and exercise capacity in patients with a subaortic right ventricle (RV) in relation to the presence of a left ventricular outflow tract obstruction (LVOTO). Methods: Retrospective chart review of adults with congenitally corrected transposition of the great arteries (ccTGA) or with a previous atrial switch procedure for complete TGA (D-TGA). A LVOTO was defined by a peak instantaneous systolic gradient > 20 mm Hg. Right and left ventricular ejection fraction (EF) were measured by cardiac magnetic resonance imaging (CMR), and exercise capacity as the predicted peak oxygen consumption (peak VO2 ) on a cycle ergometer. Results: We identified 79 clinically stable adults (age 33 ± 10 years, 70% male). Nine patients (11%) had cc-TGA and 70 patients had (89%) D-TGA. Thirteen patients (16%) had a LVOTO with a mean peak instantaneous systolic gradient of 43 ± 22 mm Hg. Patients with a LVOTO had higher left (68 ± 7% vs. 60 ± 9%, p = 0.01) and right ventricular EF (52 ± 8 vs. 46 ± 9%, p = 0.05) by CMR compared to patients without LVOTO. In a multivariate regression analysis with left ventricular EF and LVOTO as predictors, only left ventricular EF was independently associated with right ventricular EF (correlation coefficient 0.41, p < 0.01). The presence of a LVOTO was not associated with improved exercise capacity. Conclusions: In adults with a subaortic RV, a pressure loaded subpulmonary left ventricle has a beneficial effect on systemic right ventricular EF.